Van Hove Singularities: Observation of Electrically Tunable van Hove Singularities in Twisted Bilayer Graphene from NanoARPES (Adv. Mater. 31/2020). Issue 31 (4th August 2020) - Jones, Alfred J. H.; Muzzio, Ryan; Majchrzak, Paulina; Pakdel, Sahar; Curcio, Davide; Volckaert, Klara; Biswas, Deepnarayan; Gobbo, Jacob; Singh, Simranjeet; Robinson, Jeremy T.; Watanabe, Kenji; Taniguchi, Takashi; et al.
Abstract : In article number 2001656, Jyoti Katoch, Søran Ulstrup, and co‐workers apply nanoscale angle‐resolved photoemission (nanoARPES) to measure the superlattice van Hove singularity formed by the Dirac cones of twisted bilayer graphene. The photoemission experiment is performed on a device architecture that permits electrostatic tuning of the doping level, revealing the doping dependence of the singularity over a wide energy range.